Peran Gizi Terhadap Pertumbuhan Dan Perkembangan Balita - ‘Aliah Istiqomah; Kristin Masmur S; Ribby Aurellia Amali; Sulis Tiawati (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Nutrition is a substance that is very important for the growth of the human body as a fulfillment of energy found from healthy foods and drinks. Nutrition is a key factor in producing quality human resources in the future. In toddlers nutrition plays a very good role and is an important phase in human development where toddlers experience rapid physical growth, significant cognitive, social, and emotional development. The purpose of this study was conducted in order to determine the role of nutrition on development and growth in toddlers. The method used in this research is the literature review method, which is research conducted to collect data from various sources to find literature such as journals, books, newspaper articles, the internet or websites. The role of nutrition for development and growth in infancy is very important, because in infancy this is the initial stage in the process of training and development of the human body.